Advances in the Drugs Treatment of Psoriatic Arthritis - LU Chaofan; LENG Xiaomei (Xiehe Yixue Zazhi)
Psoriatic arthritis (PsA), an inflammatory articular disease closely associated with psoriasis, is characterized by a wide range of symptoms including skin lesion, peripheral and axial joint involvement, enthesitis, and dactylitis. In recent years, significant advancements have been made in the treatment of PsA, promoting continuous improvement in patient outcomes. This article aims to comprehensively review the current status of drug treatment for PsA, encompassing not only new clinical evidence for conventional synthetic disease-modifying antirheumatic drugs(csDMARDs) but also an in-depth exploration of biologics or targeted synthetic disease-modifying antirheumatic drugs(tsDMARDs) against various targets in recent years. The objective of this study is to enhance clinicians' understanding of treatment strategies for PsA and provide more precise and effective treatment options for patients.